DIGITAL LITERACY AND POLITICAL DISINFORMATION: A CRITICAL STUDY OF IKIP PGRI BOJONEGORO STUDENTS ON TikTok - Lestari, Sely Ayu; Saputri, Ernia Duwi; ., Zuhad (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2025)
Digital literacy is a key competency needed by students to address the rise of political disinformation in the digital space, including on the TikTok platform. This qualitative study aims to analyze the role of digital literacy in shaping critical attitudes toward political disinformation among IKIP PGRI Bojonegoro students. Data were obtained through in-depth interviews, observations, and documentation from relevant academic sources. The results of the study indicate four main roles of digital literacy: 1) changing students' patterns in accessing and interpreting political information; 2) improving verification skills through source evaluation and fact-checking; 3) strengthening students' resilience to algorithmic manipulation, emotional bias, and viral effects; and 4) encouraging students' critical and ethical participation in responding to political content on TikTok. This study confirms that the higher students' digital literacy, the stronger their ability to recognize and reject political disinformation. These findings contribute to strengthening digital literacy education in higher education.